New Transit Observations for HAT-P-30 b, HAT-P-37 b, TrES-5 b, WASP-28 b, WASP-36 b and WASP-39 b - Maciejewski, G. (2016)
We present new transit light curves for planets in six extrasolar planetary systems. They were acquired with 0.4–2.2 m telescopes located in west Asia, Europe, and South America. When combined with literature data, they allowed us to redetermine system parameters in a homogeneous way. Our results for individual systems are in agreement with values reported in previous studies. We refined transit ephemerides and reduced uncertainties of orbital periods by a factor between 2 and 7. No sign of any variations in transit times was detected for the planets studied.